A numerical methodology for assessing the hydrokinetic energy potential in natural channels - Gopie, Kaajal Rohini (2022)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2022.